Review of the genus Brachytarsophrys (Anura: Megophryidae), with revalidation of Brachytarsophrys platyparietus and description of a new species from China - Li, Yao (Science Press, 2020)

(untitled) (Zool Res)
The genus-level recognition of monophyletic short-legged toads (Brachytarsophrys) has been recently implicated in the taxonomic debate of Megophrys sensu lato. In the present study, Brachytarsophrys is reasonably regarded as a distinct genus based on significant morphological differentiations and recent molecular analyses. Furthermore, a comprehensive review of this genus is performed, with two species groups proposed based on morphological differences and phylogenetic relationships. Particularly, Brachytarsophrys platyparietus is removed as a synonym of Brachytarsophrys carinense and considered a valid species due to significant genetic divergence and distinct morphological differences. In addition, a new species, Brachytarsophrys orientalis sp. nov., is described based on a series of specimens collected from southeastern China. This work takes the member species of the genus Brachytarsophrys to seven, suggesting that the diversity of Brachytarsophrys is underestimated. In addition, the genus levels of other monophyletic groups within the subfamily Megophryinae are discussed.